Training on Making Merdeka Curriculum Teaching Modules Based on Differentiation Learning for Teachers in Dempo Utara District: Pelatihan dan Pendampingan Pembuatan Modul Ajar Kurikulum Merdeka Berbasis Pembelajaran Berdiferensiasi bagi Guru-Guru di Kecamatan Dempo Utara Kota Pagar Alam - Susiloningsih, Esti; Fathurohman, Apit; Kistiono; Auliya Kurdiati, Lintang; Hadi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The low level of teacher skills in creating independent curriculum teaching modules based on differentiated learning in Indonesia as well as in North Dempo District means that the quality of learning is not yet optimal. The community service carried out in Pagar Alam City is a form of effort to increase teacher professionalism in creating independent curriculum teaching modules. The aim of implementing community service is to increase teachers' understanding and skills in creating independent curriculum teaching modules based on differentiated learning. The methods used in implementing community service are socialization, training, practice, mentoring, and evaluation. This training material was carried out in two stages, where the first stage focused more on providing information about material related to teaching modules, differentiated learning, and differentiated learning-based teaching modules. The second stage of training focused on creating independent curriculum teaching modules. Community service program training participants were very satisfied with the training in creating independent curriculum teaching modules based on differentiated learning.